Determinants of school-going adolescent girls’ health and nutritional status in district Malir, Karachi: a baseline cross-sectional study - Zafar, Saira; Shaikh, Babar Tasneem; Malik, Zoha Imtiaz; Ahmad, Abdul Momin Rizwan (Frontiers in Nutrition, 2025)
IntroductionAdolescence is a phase of life marked by rapid growth. Adequate nutrition is essential during this developmental stage, leading to significant physical performance, improved cognitive ability, and productivity. Improving adolescent girls’ nutrition is crucial for breaking the intergenerational cycle of malnutrition, but research in Pakistan has largely focused on children under five and pregnant women, often neglecting this vulnerable group.ObjectiveThis study aimed to determine the contextual and sociodemographic factors contributing toward undernutrition to improve the health and nutritional status of adolescent girls.MethodsA school based cross sectional study was conducted as the baseline survey for a mixed methods study leading to a pilot cluster randomized controlled trial. n = 84 girls (10–14 years) from two public schools were selected by simple random sampling. Data were collected through a structured questionnaire including socio demographic profile, anthropometric measurements, dietary patterns, preferences, safe water and hygiene practices, access to health care facilities, and understanding of malnutrition-related symptoms. The data collected were analyzed through SPSS version 27.0. The chi-square test was used to determine the association between the two BMI categories; underweight and normal weight, and various socio-demographic variables.ResultsAmong the total of 84 adolescent girls, overall mean height was 143.9 ± 8.1 cm and mean weight was 34.4 ± 6.9 kg, while mean BMI was 16.4 ± 2.2 kg/m2. 86.9% of girls were underweight, whereas 13.1% had a normal BMI. The z-scores for both height-for-age and BMI-for-age were in negative values, i.e., −1.62 ± 0.89 and −1.18 ± 1.05, respectively.ConclusionFindings of this study demonstrated that the high burden of underweight among school-going adolescent girls needs targeted approaches like nutrition education interventions to enhance awareness about healthy dietary behaviors, food preferences, and ensuring access to safe, sufficient, and healthy diet.RecommendationA multipronged approach is required to improve health and nutritional status of adolescent girls by involving individuals, families, education sector, health and other relevant sectors. Larger scale studies are still required for better understanding of the issue and to guide in designing targeted programs to address specific needs of this particular age group.